2012
DOI: 10.1038/bjc.2012.335
|View full text |Cite
|
Sign up to set email alerts
|

Increased MET and HGF gene copy numbers are associated with trastuzumab failure in HER2-positive metastatic breast cancer

Abstract: Background:To investigate whether copy number gain of MET or hepatocyte growth factor (HGF) affect trastuzumab sensitivity in HER2-positive metastatic breast cancer (MBC).Methods:We analysed 130 HER2-positive MBC treated with trastuzumab-based therapy. MET and HGF gene copy numbers (GCN) were assessed by fluorescence in situ hybridisation (FISH) in primary breast cancer samples. Receiver operating characteristic analysis was applied to find the best cutoff point for both MET and HGF GCN.Results:MET FISH-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 39 publications
1
74
2
1
Order By: Relevance
“…c-Met activates its downstream effectors of the Ras-mitogen-activated protein kinase (MAPk) and phosphatidylinositol 3-kinase (PI3k)-Akt pathways to promote the invasive growth characteristic of malignancies (35,36). Also in breast cancer, disruption of the c-Met pathway has been shown to contribute to worse prognosis (20,37) and confer resistance to endocrine therapy or trastuzumab treatment (38)(39)(40). In addition to c-Met, its ligand HGF is also suggested to be an independent prognostic parameter for breast cancer (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…c-Met activates its downstream effectors of the Ras-mitogen-activated protein kinase (MAPk) and phosphatidylinositol 3-kinase (PI3k)-Akt pathways to promote the invasive growth characteristic of malignancies (35,36). Also in breast cancer, disruption of the c-Met pathway has been shown to contribute to worse prognosis (20,37) and confer resistance to endocrine therapy or trastuzumab treatment (38)(39)(40). In addition to c-Met, its ligand HGF is also suggested to be an independent prognostic parameter for breast cancer (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…MET amplification has not been reported to be common in breast cancer, in the present study only 8% was found (Paper I) [138,139]. However, copy gain has been reported for MET in 27% HER2-positive metastatic breast cancer cases, as in the pre-and post-menopausal patients here, unrelated to subtype [140]. HGF copy gain was previously reported in 65% of the HER2-positive cases, considerably higher than the 21-27% found in all patients in the two cohorts, here [140].…”
Section: Genes Of Interest In Breast Cancer Tumourscontrasting
confidence: 48%
“…However, copy gain has been reported for MET in 27% HER2-positive metastatic breast cancer cases, as in the pre-and post-menopausal patients here, unrelated to subtype [140]. HGF copy gain was previously reported in 65% of the HER2-positive cases, considerably higher than the 21-27% found in all patients in the two cohorts, here [140]. Chromosome 7q amplification has previously been reported in breast cancer [143].…”
Section: Genes Of Interest In Breast Cancer Tumoursmentioning
confidence: 46%
“…In a study conducted Minuti and colleagues, high gene copy numbers of MET and HGF correlated with poor outcomes and resistance to trastuzumab in HER2-positive breast cancers (46). Shattuck and colleagues demonstrated that trastuzumab-resistant primary cell lines and primary tumors also exhibited elevated expression of MET and HGF (47).…”
Section: Erbb2-positive Malignanciesmentioning
confidence: 99%